Radiation Safety in Catheterization Laboratories: Gaps in Knowledge, Attitudes, and Practices among Cardiologists – A Cross-sectional Study in Tertiary Care Cardiac Center - D. Narendran; Bharath Raj Kidambi; A. C. Nagamani; K. H. Srinivas; K. S. Ravindranath (Journal of Indian College of Cardiology)
Background: Cardiac catheterization laboratories (Cath Labs) extensively use ionizing radiation, exposing healthcare professionals to occupational hazards. Despite established safety guidelines, significant gaps in knowledge, attitudes, and practices (KAP) regarding radiation protection persist, particularly in developing countries. Methods: This cross-sectional study, conducted in 2024 at a tertiary cardiac care center in South India, utilized a prevalidated KAP questionnaire distributed to all Cath Lab professionals. Of those approached, 77 participants, including 49 residents and 28 consultants, responded. The survey assessed radiation safety knowledge, perceptions of occupational risks, and protective practices. Data were analyzed using SPSS v28.0, with P < 0.05 considered significant. Results: Eighty-seven percent of participants reported no formal radiation safety training, and only 46.75% correctly identified the annual dose limit (20 mSv). Familiarity with the inverse square law was similarly low (46.75%). While 52% strongly believed radiation exposure impacts career longevity, practices were inconsistent: 36.36% never used lead eyewear, and 76.62% did not monitor cumulative exposure. Consultants demonstrated superior knowledge and compliance compared to residents, with significant differences in training and adherence. Conclusion: This study highlights substantial gaps in radiation safety KAP among Cath Lab professionals. Structured training programs, ergonomic protective equipment, and automated monitoring systems are crucial for improving compliance. Mentorship and regular audits can promote a safety-centric culture. While advancements in shielding technologies hold promise, strict adherence to existing safety protocols remains vital to protect healthcare workers and ensure procedural efficacy.